Local antiquities, local identities : art, literature and antiquarianism in Europe, c. 1400-1700 - Christian, Kathleen (Kathleen Wren), 1971-; De Divitiis, Bianca (Manchester University Press, 2019)
Examining a range of antiquarian practices - history-writing, archaeological investigations, works of art, architecture and literature - that emerged in early modern Europe, this text challenges the idea of a single 'Renaissance'. It assembles essays on local antiquities in Spain, Portugal, France, Britain, Italy, the Netherlands and Poland.